2009
DOI: 10.1002/fut.20405
|View full text |Cite
|
Sign up to set email alerts
|

The information content of implied volatility: Evidence from Australia

Abstract: This study develops an implied volatility index for the Australian stock market, termed as the AVX, and assesses its information content. The AVX is constructed using S&P/ASX 200 index options with a constant time‐to‐maturity of three months. It is observed that the AVX has a significant negative and asymmetric relationship with S&P/ASX 200 returns. When evaluating the forecasting power of the AVX for future stock market volatility, it is found that the AVX contains important information both in‐sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(32 citation statements)
references
References 22 publications
1
29
1
1
Order By: Relevance
“…Dowling and Muthuswamy (2005) using data from the Australian options market and the Black-Scholes option pricing model find that the implied volatility index performs poorly compared to historical volatility. In contrast to their study Frijns et al (2008) find from the Australian data that the volatility index contains important information both in sample and out of sample. Giot (2005a) demonstrates that volatility forecasts based on the VIX/VXN indexes have the highest information content, both in the volatility forecasting and market risk assessment frameworks.…”
Section: India's Volatility Indexcontrasting
confidence: 69%
See 1 more Smart Citation
“…Dowling and Muthuswamy (2005) using data from the Australian options market and the Black-Scholes option pricing model find that the implied volatility index performs poorly compared to historical volatility. In contrast to their study Frijns et al (2008) find from the Australian data that the volatility index contains important information both in sample and out of sample. Giot (2005a) demonstrates that volatility forecasts based on the VIX/VXN indexes have the highest information content, both in the volatility forecasting and market risk assessment frameworks.…”
Section: India's Volatility Indexcontrasting
confidence: 69%
“…Subsequent studies by Skiadopoulos (2004) for the Greek market and Ting (2007) for the Korean market provide evidence on the asymmetric relationship between market returns and the changes in volatility index. However, Dowling and Muthuswamy (2005) find no asymmetric response in the Australian market, while Frijns et al (2008), using data over a longer period, provide mixed evidence for the same. Siriopoulos and Fassas (2009) report absence of a statistically significant asymmetric relationship for some of the volatility indices like the Russel 2000 volatility index, VIX, VXN and Montreal implied volatility index (MVX).…”
Section: India's Volatility Indexmentioning
confidence: 94%
“…With respect to European volatility indices- Siriopoulos and Fassas (2008) for VFTSE (UK); González and Novales (2009) for VDAX-NEW (Germany), VSMI (Switzerland) and VIBEX (Spain); and Siriopoulos and Fassas (2012) for GRIV (Greece)-the findings are also consistent. Ting (2007), Frijns, Tallau, andTourani-Rad (2010) and Kumar (2012) extend the empirical evidence to Korea, Australia and India, respectively. Moreover, most studies show that the relationship between returns and implied volatility is also asymmetric: a rise (fall) in implied volatility (the equity market) has a stronger opposite effect on equity market returns (implied volatility) than does a decrease (increase) in implied volatility (equity market).…”
Section: The Relationship Between Volatility Indices and Market Returnsmentioning
confidence: 92%
“…Hence, at this point one can say that implied volatility rises for the negative return shocks and falls following the positive return shocks. The literature evidences in favor of asymmetric relation (Bates, 2000;Bollerslev & Zhou, 2006;Dennis et al, 2006;Dowling & Muthuswamy, 2005;Ederington & Guan, 2010;Fleming et al, 1995;Frijns et al, 2010;Giot, 2005;Pan, 2002;Poteshman, 2001;Schwert, 1989Schwert, , 1990.…”
Section: Introductionmentioning
confidence: 95%
“…Dowling & Muthuswamy, 2005;Ederington & Guan, 2010;Frijns, Tallau, & Tourani-Rad, 2010;Giot, 2005) has shown that asymmetric impact holds on the implied volatility. The systematic foundation of asymmetric relationship between implied volatility and the stock market returns was first given by Schwert (1989Schwert ( , 1990 and Fleming et al (1995) they find significant negative and asymmetric relation between volatility and returns.…”
Section: Introductionmentioning
confidence: 97%